Abraham Lincoln without borders : Lincoln's legacy outside the United States - Tripathy, Jyotirmaya; Rath, Sura P.; Pederson, William D. (Pencraft International, 2010)
Papers presented at an international seminar held at Chennai during 19-20 December 2009.